2021
DOI: 10.3390/cancers13122975
|View full text |Cite
|
Sign up to set email alerts
|

Meta-Analysis of the Accuracy of Abbreviated Magnetic Resonance Imaging for Hepatocellular Carcinoma Surveillance: Non-Contrast versus Hepatobiliary Phase-Abbreviated Magnetic Resonance Imaging

Abstract: We aimed to determine the performance of surveillance abbreviated magnetic resonance imaging (AMRI) for detecting hepatocellular carcinoma (HCC), and to compare the performance of surveillance AMRI according to different protocols. Original research studies reporting the performance of surveillance AMRI for the detection of HCC were identified in MEDLINE, EMBASE, and Cochrane databases. The pooled sensitivity and specificity of surveillance AMRI were calculated using a hierarchical model. The pooled sensitivit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 19 publications
(22 citation statements)
references
References 43 publications
(118 reference statements)
0
22
0
Order By: Relevance
“…NC-AMRI with or without in- and opposed-phase T1W imaging had non-significant differences in sensitivity and specificity [ 19 ]. In another meta-analysis, comparing hepatobiliary phase CE-AMRI and NC-MRI for detection of HCC, sensitivity was higher in favor of CE-MRI over NC-AMRI, but specificity was lower (sensitivity 87% vs. 82% and specificity 93% vs. 98%, respectively) [ 30 ]. However, some of the included studies in this review were not performed in a surveillance setting for HCC detection.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…NC-AMRI with or without in- and opposed-phase T1W imaging had non-significant differences in sensitivity and specificity [ 19 ]. In another meta-analysis, comparing hepatobiliary phase CE-AMRI and NC-MRI for detection of HCC, sensitivity was higher in favor of CE-MRI over NC-AMRI, but specificity was lower (sensitivity 87% vs. 82% and specificity 93% vs. 98%, respectively) [ 30 ]. However, some of the included studies in this review were not performed in a surveillance setting for HCC detection.…”
Section: Discussionmentioning
confidence: 99%
“…However, some of the included studies in this review were not performed in a surveillance setting for HCC detection. In spite of the fact that some limited differences in sensitivity and specificity between different AMRI protocols for surveillance of HCC were reported, the sensitivity and specificity are generally much better compared with US [ 3 , 7 , 9 , 13 , 19 , 25 , 26 , 27 , 29 , 30 , 31 ]. Furthermore, our results concur with these reports.…”
Section: Discussionmentioning
confidence: 99%
“…The previous meta-analysis revealed that the pooled sensitivity and specificity were 0.86-0.87 and 0.94-0.96, respectively, with an AUROC of 0.95 for the detection of HCC using gadoxetic acid abbreviated MRI. 82,83 Another meta-analysis of gadoxetic acid abbreviated MRI reported an excellent inter-reader agreement (κ = 0.98) for the detection of HCC. 84 Few papers have examined the usefulness of abbreviated MRI for searching liver metastases.…”
Section: Clinical Significance Of Liver Mrimentioning
confidence: 99%
“…[223] To leverage the performance of MRI with limited costs and procedural requirements, abbreviated MRI (AMRI) has been actively explored to develop a protocol tailored as an HCC screening test. [224,225] AMRI protocols can be classified into three types: noncontrast-enhanced, hepatobiliary contrast-enhanced, and dynamic extracellular contrast-enhanced AMRI. [226] The overall patient-level sensitivity and specificity of AMRI for HCC detection were 86% and 94%, respectively, in a meta-analysis, regardless of the AMRI type, presence of cirrhosis, and HCC etiology.…”
Section: Imaging-based Hcc Early-detection Testsmentioning
confidence: 99%